(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2022)
Wastewater affects concrete structures, causing corrosion and disintegration of concrete, and then corrosion of iron inside concrete due to the presence of salts and chemicals in wastewater. It causes a lack of cohesion between it and the cement paste, and the concrete may crack and collapse. In addition, the presence of salts such as sulfates, chlorides, and sometimes carbonates has adverse effects on concrete. A number of cubes were taken and placed in a basin containing pure water for testing. A number of cubes were placed in a basin containing sewage water, and a number of cubes were placed in basins containing these solutions AL2O3 (Aluminium oxide), SiO2 (Silicon dioxide), TiO2 (Titanium dioxide), Fe2O3 (Iron oxide), K2O (potassium oxide), MgO (Magnesium oxide), SO3 (Sulfur trioxide), CaO (Calcium oxide), MnO (Manganese oxide), P2O5 (Phosphorus pentoxide)). and after checking the results in 7, 28, 56, and 90 days. The result of the test was that it appears the elements that increase the compressive strength of concrete are (AL2O3, SiO2, Fe2O3, and TiO2) with a rate of 30% at 28 days, 39% at 56 days, and 43% at 90 days. At the same time, the elements that reduce the compressive strength of concrete are (K2O, MgO, SO3, P2O5, MnO, CaO, and BOD) with a rate of 18% at 28 days, 24% at 56 days, and 29% at 90 days.